Caracterización de las especificaciones del material de empaque y envase de BRIMODIN* SOO mg tabletas efervescentes elaboradas en el área de control de calidad del Laboratorio IQFARMA - Santos Mendoza, Amado Agustín (2015)
ABSTRACTThis report is the identification of key quality characteristics of packaging material and packaging of effervescent tablets 600 mg BRIMODIN® laboratory IQFARMA. The research question was to assess whether the packaging material and packaging of effervescent tablets 600 mg BRIMODIN® complies with the specifications established by the area of quality control. For this first designed the specifications of packaging materials and packaging for the product BRIMODIN® 600 mg effervescent tablets, from the current pattern art provided by the area of regulatory affairs and quality certificates provided by the supplier. Then we proceeded to sample the materials brought in packaging control area and assess whether they comply with the specifications. From the results it was concluded that: The quality characteristics of the mam materials as packaging material specifications and packaging of effervescent tablets 600 mg BRIMODIN® laboratory IQFARMA are: description, size, color, text, appearance, material thickness , weight, functionality, tightness, anchor test printing, storage and sampling. Also, packaging materials and packaging of effervescent tablets 600 mg BRIMODIN" used in the laboratory IQFARMA meet specifications